Students’ Digital Literacy In English Learning At Senior High School - Salam Dimyati, Muhammad Firos (International Journal of English Language and Pedagogy, 2024)
Skills in English both spoken and written are important for students to master. Academic Speaking is an advanced course that aims to train students to be able to communicate in English in an academic context. The implementation of this differentiated instruction allows students to have English speaking skills because this learning adapts to students' needs, interests, readiness and potential. Apart from that, the intervention in this learning in terms of content, processes and products also allow students' speaking skills to improve. The aim of this research is to describe the extent to which the implementation of differentiated instruction can improve students' English skills, especially in the area of ​​speaking skills in the Academic Speaking class, English Language Education Study Program, FKIP, Bengkulu University and to find out students' opinions regarding the application of this learning in this class. Meanwhile, the research design is Classroom Action Research (PTK) whose activity stages include: planning, implementation, evaluation and reflection. The results of the research show that the application of differentiated learning provides improvements in students' speaking skill scores in academic speaking classes. The average score of students' speaking skills is 82 (A-) which exceeds research indicators which only target an average score of B. There are several recommendations or suggestions given, especially to students, lecturers and curriculum developers regarding the implementation of differentiated learning.